Job stress, job performance and job satisfaction of teaching personnel of Centro Escolar University : basis for an intervention program - Usal, Delsa F. (Manila : National University, 2013)
This study determines the effects of stress of teaching of Centro Escolar University. It will be limited to 100 teaching personnel who will be chosen through random sampling technique from the total population of the respondents during the school year 2013-2014.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.